CORRELATION BETWEEN STUDENT ANXIETY AND SPEAKING PERFORMANCE - Rahmayati, Ai; Parmawati, Aseptiana; Syathroh, Isry Laila; Nurhasanah, Imas (PROJECT (Professional Journal of English Education), 2024)
This study aims to determine whether there is a relationship between the level of student anxiety with the performance of students speaking in front of the class. This research used a quantitative method in the correlation model. The population in this study was Junior High School, and the sample used for this study was grade 9 students with a total of 32 students. The instruments used are questionnaires and tests. The collected data, both questionnaire scores and speaking test scores, were then analyzed through SPSS. The results of the data significance analysis were 0.990. Hypothesis attempts to explain N.Sig > 5% and for these effects, the null hypothesis in this observation is accepted. This issue suggests that students' anxiety and speaking performance in front of the class are not correlated. It could be concluded that, there is no correlation between student anxiety and students' speaking performance. Based totally on these outcomes, the strength of this correlation is moderate. From the outcomes of this observation, it could be stated that language anxiety hurts students' speaking performance. Consequently, students with low anxiety have a good speaking rating, and students with high anxiety may have a low speaking rating.